Description of ichthyosaur remains from the Lower Cretaceous Agrio Formation (Neuqu en Basin, west-central Argentina) and their paleobiological implications - Lazo, Darío G. (2018)
Fil: Lazo, Darío G. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias Geológicas. Instituto de Estudios Andinos “Don Pablo Groeber". Buenos Aires, Argentina